2020
DOI: 10.1002/ppul.25226
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory outcomes of “new” bronchopulmonary dysplasia in adolescents: A multicenter study

Abstract: Objective Long‐term respiratory consequences of bronchopulmonary dysplasia (BPD) in preterm infants born in the post‐surfactant era (“new” BPD) remain partially unknown. The present study aimed to evaluate the respiratory outcomes of “new” BPD in adolescents who were born preterm. Methods This multicenter, cross‐sectional study included 286 adolescents born between 2003 and 2005 (mean age: 14.2 years); among them, 184 and 102 were born extremely preterm (EP; <28 weeks' gestation) and moderate–late preterm (32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 39 publications
1
19
0
4
Order By: Relevance
“…Once the responses from contacted study authors were collated, 18 articles satisfied the inclusion criteria. 14 , 15 , 16 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 15 studies reported expiratory airflow data from MLP participants, 14 , 15 , 16 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 eight of which compared MLP participants with term-born controls. 14 , 15 , 16 , 37 , 38 , 39 , 40 , 41 , 42 Three studies were not eligible for meta-analysis, with two unable to provide z-score data, 29 , 30 and one with indices of impulse oscillometry only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the responses from contacted study authors were collated, 18 articles satisfied the inclusion criteria. 14 , 15 , 16 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 15 studies reported expiratory airflow data from MLP participants, 14 , 15 , 16 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 eight of which compared MLP participants with term-born controls. 14 , 15 , 16 , 37 , 38 , 39 , 40 , 41 , 42 Three studies were not eligible for meta-analysis, with two unable to provide z-score data, 29 , 30 and one with indices of impulse oscillometry only.…”
Section: Resultsmentioning
confidence: 99%
“… 14 , 15 , 16 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 Study Region MLP Birth Characteristics Sex (% Male) Assessment Gestational Age (wk) Birthweight (g) MLP Term MLP Age (years) No. of Participants Pulmonary Function Tests Conducted Spirometry Reference Values Mean SD Range Mean SD Mean SD Range MLP Term Aoyama et al, 2021 31 a USA 33.9 1.3 2189 592 72 NA 7.3 1.8 7 NA Spirometry GLI 2012 Arroyas et al, 2020 36 Spain 34.2 1.2 2014 526 51.4 NA 14.1 74 NA ...…”
Section: Methodsmentioning
confidence: 99%
“…BPD is also burdened by long-term consequences, which include impaired lung function and architecture, recurrent respiratory infections and poor neurodevelopmental outcomes. Respiratory difficulties may continue well into adolescence and adulthood 9–12. Mortality rate is up to 3% during first admission in infants diagnosed with severe BPD and 20% within 2 years of life in infants requiring tracheostomy 13–15…”
Section: Introductionmentioning
confidence: 99%
“…BPD is also burdened by long-term consequences, which include impaired lung function and architecture, recurrent respiratory infections, and poor neurodevelopmental outcomes. Respiratory di culties may continue well into adolescence and adulthood (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%